CONTEMPORARY PROBLEMS IN THE PSYCHOLOGY OF CHILDREN UNDER FIVE YEARS AND THEIR SOLUTIONS - Siddiqova Feruza Baxtiyorovna (Modern American Journals, 2025)
The psychology of children under the age of five has become one of the most critical areas of study in developmental science and applied psychology, largely because the earliest years of life represent a uniquely sensitive period in which cognitive, emotional, and social foundations are established that shape later functioning across the life course. Numerous contemporary problems affect the psychological well-being and developmental trajectories of children in this age group, including rapid sociocultural transitions, economic pressures on families, increased exposure to digital technologies, global health crises, disparities in early childhood education, and insufficient parental awareness of developmental needs. This paper seeks to analyze these pressing challenges systematically, drawing on recent empirical findings from developmental psychology, pediatrics, psychiatry, and early childhood education. Methodologically, the study synthesizes available literature, including meta-analyses, cohort studies, and program evaluations, while also proposing integrative solutions grounded in evidence-based interventions such as parent training, early childhood education reform, community support structures, and policy innovations. The results highlight that unresolved psychosocial stressors, digital overexposure, and lack of attachment security represent core threats to psychological development before the age of five, whereas targeted interventions focused on strengthening parent-child interaction, equitable access to preschool environments, and culturally sensitive psychological guidance yield demonstrable benefits. In the discussion, the study emphasizes that solving these problems requires a holistic framework that combines micro-level strategies at the family and clinical level with macro-level strategies at the societal and policy level. The overall conclusion underscores that the mental health of children under five must be regarded not merely as an individual or familial matter but as a societal responsibility whose investment returns are seen in educational outcomes, social stability, and long-term economic productivity.
Keywords: Early childhood psychology; developmental challenges; under-five children; parental influence; digital exposure; attachment theory; educational disparities; early inte.